Slit is the midline repellent for the robo receptor in Drosophila. - Kidd, T.; Bland, K.S.; Goodman, C.S. (Cell, 1999)
Previous studies suggested that Roundabout (Robo) is a repulsive guidance receptor on growth cones that binds to an unknown midline ligand. Here we present genetic evidence that Slit is the midline Robo ligand; a companion paper presents biochemical evidence that Slit binds Robo. Slit is a large extracellular matrix protein expressed by midline glia. In slit mutants, growth cones enter the midline but never leave it; they abnormally continue to express high levels of Robo while at the midline. slit and robo display dosage-sensitive genetic interactions, indicating that they function in the same pathway. slit is also required for migration of muscle precursors away from the midline. Slit appears to function as a short-range repellent controlling axon crossing of the midline and as a long-range chemorepellent controlling mesoderm migration away from the midline.